Hubungan Tinggi Badan Ibu dan Riwayat Pemberian MP-ASI dengan Kejadian Stunting pada Balita Usia 24-59 Bulan - Nur Hadibah Hanum (Amerta Nutrition, 2019)
Background: Stunting is a short body condition that occurs due to a lack of intake of various nutrients. Maternal body size may be one of the factors causing stunting in children.Objective: The purpose of this study was to analyze the relationship between maternal height and complementary feeding history with The Incidence of Stunting on Age 24-59 months.Methods: The cross-sectional study was carried out in Maron District, Probolinggo Regency.The sampling was carried out by multistage random sampling method with a sample of 97 pairs of mothers and under five years old children. Independent variables observed were maternal stature and complementary feeding history which consists of the age of first given food, complementary feeding texture, frequency, and amount of complementary food given. The dependent variable was the occurrence of stunting. Data analysis used in this study was chi-square test.Results: This study shows the results of a significant association between complementary feeding at the age of first given food at the age of first given food that is before, during, or after a 6 month old with the incidence of stunting p=0.012. On the other hand, there was no correlation between complementary feeding texture p=0.788, frequency p=0.208, amount of complementary food given p=0.107, and maternal height p=0.704 with the incidence of stunting.Conclusion: In conclusion, complementary feeding history was related to the incidence of stunting in infants, whereas complementary feeding texture, frequency, amount of complementary food and maternal height had no impact on the incidence of stunting in infants.ABSTRAKLatar Belakang: Stunting merupakan keadaan tubuh pendek akibat dari kekurangan asupan berbagai macam zat gizi. Ukuran tubuh ibu mungkin menjadi salah satu faktor penyebab terjadinya stunting pada anak.  Tujuan: Tujuan penelitian ini untuk menganalisis hubungan antara tinggi badan ibu dan riwayat pemberian makanan pendamping air susu ibu (MP-ASI) dengan kejadian stunting pada balita usia 24-59 bulan.Metode: Menggunakan cross sectional dilakukan di Kecamatan Maron Kabupaten Probolinggo. Pengambilan sampel dilakukan secara multistage random sampling dengan besar sampel 97 ibu-balita. Variabel bebas yang diamati antara lain tinggi badan ibu dan riwayat pemberian MP-ASI yang terdiri dari usia pertama kali diberikan makanan, bentuk, frekuensi, dan jumlah MP-ASI sedangkan variabel tergantung adalah kejadian stunting. Analisis data yang digunakan adalah uji chi-square.Hasil: Hasil penelitian menunjukkan bahwa terdapat hubungan yang bermakna antara pemberian makanan pendamping ASI pada usia pertama kali diberikan makanan yaitu sebelum, saat, atau sesudah bayi berusia 6 bulan dengan kejadian stunting p=0,012 sebaliknya tidak ada hubungan antara bentuk p=0,788, frekuensi p=0,208, jumlah p=0,107 dan tinggi badan ibu p=0,704, dengan kejadian stunting.Kesimpulan: Kesimpulan dari penelitian ini adalah riwayat pemberian MP-ASI pada faktor usia balita pertama kali diberikan MP-ASI berhubungan dengan kejadian stunting pada balita, sedangkan bentuk, frekuensi, jumlah makanan yang diberikan serta tinggi badan ibu balita tidak memiliki hubungan dengan kejadian stunting.